Leaving no one behind: How women seize control of wheat-maize technologies in Bangladesh - Farnworth, Cathy Rozel; Jafry, Tahseen; Rahman, S.; Badstue, Lone B. (Informa UK Limited, 2020)
Bangladesh is strongly committed to the “leave no one behind” principle of the UN’s Sustainable Development Goals. However, social norms and institutional biases in agricultural organisations can prevent indigenous peoples and women from participating in wheat–maize innovation processes, as they rarely meet the requisite criteria: su?cient land, social capital or formal education. The GENNOVATE (Enabling Gender Equality in Agricultural and Environmental Innovation) research initiative in Bangladesh shows that indigenous Santal women are obtaining access to and bene?ting from wheat–maize innovations, enabling low-income Muslim women to bene?t as well.